Immunoprophylaxis of Cancer Cervix - Bhattacharjee, Seema (Journal of Brahmanbaria Medical College, 2026)
Background: Cervix is an integral part of anatomy, physiology, pathology including obstetrics and gynaecology.Anatomical continuity, contiguity with parametrium and urology e.g. bladders base and ureter including endocrine influences on cervical mucus responsible for diagnosis of ovulation followed by pregnancy and childbirth. Obstetrics injury, postpartum lochia, reduced cellular immunity, opportunistic infection favourable infusion and inflammation by organisms sometimes responsible for producing recurrent attack may be a probability of persistence of infection and chronic morbidity. The progress and Challenges in the development of immunopropylaxis approach for the prevention, the advantages of HPV vaccination and treatment of cervical cancer are summarised in this review article. Methodology: This review to published studies and articles by using Google. Search strategy using appropriate key words and title. Conclusion: Vaccinations against all HPV are available but financial issues are the prime barrier to HPV vaccination. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 30-35